Adulticidal synergy of two plant essential oils and their major constituents against the housefly Musca domestica and bioassay on non-target species - Mayura Soonwera; Tanapoom Moungthipmalai; Cheepchanok Puwanard; Sirawut Sittichok; Jirisuda Sinthusiri; Hataichanok Passara (Heliyon, 2024)
anethole can be an excellent, natural, sustainable housefly adulticidal agent.
Keywords: Insect Pest Control Strategies; Insect and Pesticide Research; Insect Utilization and Effects